An investigation into sustainable construction stimulators and blockers - Osmani, M (European Journal of Sustainable Development, 2014)
The UK Government has been using a combination of regulation, economic instruments and voluntary agreements to meet targets of ethical, social and environmental performance in driving the climate change agenda. The UK is the first country worldwide to set a legally binding 80% greenhouse-gas emissions reduction target by 2050. The built environment in the UK is responsible for about 40% of carbon emissions, 32% of solid waste generation, 20% of water effluents, and 40% of all energy used. As such, the construction industry has been targeted to facilitate the transition to a low-carbon economy.Indeed, sustainability within the built environment has become the forefront of all sustainable development policies in the UK. However; various studies have outlined the difficulty of translating the UK’s 80% greenhouse-gas emissions reduction target to a micro level such as construction projects. This research engaged the top 100 UK contractorsto investigate stimulators that drivethe implementation of sustainability in their projects,and assess associated blockers. Findings reveal that sustainability requirements driven by financial and business were viewed by participating contractors as being the key motivators in construction projects. Corporate Social Responsibility (CSR) was viewed as a vehicle to improve social and environmental dynamics of sustainability through local community support initiatives, which in turn has increased companies’ opportunities to secure new projects, particularly from public clients. On the other hand, respondents called for clearer and inclusive legislation; increased awareness; enhanced communication and coordination among project stakeholders; and widespread sharing and dissemination of sustainable construction best practice data. Keywords: UK; contractors; sustainable construction; stimulators; blockers.